LANGUAGE CHOICE PERFORMED BY SASAK TEENAGERS: A CASE STUDY AT MATARAM 2023 - Ilham Hafis Zulmiyadi; Mahyuni; Muh. Isnaeni; Kamaluddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Language is a communication tool between individuals to interact with each other. Sasak teenagers these days are more using Bahasa rather than Sasak language. It seems that Sasak language begins to be abandoned by Sasak teenagers in Mataram. Therefore, this study aims to identity and describe the factors that influences Sasak teenagers rarely use Sasak language as their main language and role of parents in influencing teenagers’ language choice. The method utilized in this study was ethnography. The techniques used for data collection included observation, participant, formal and informal interviews with participants and video recording of human activities, and collection of relevant sources of information. There are 12 teenagers were interviewed in this study. Based on the field data, there are four factors that influenced Sasak teenagers included environment, media, global identity and family background. In the context of decreasing use of Sasak language, the role of parents is still an important but over time this influence decreased and was changed with greater interaction with the social environment influencing teenagers’ language choices.